Antibacterial Activity Test of Secang Wood (Caesalpinia sappan L.) Ethanol Extract Against Streptococcus mutans - Listiani, Febri Intan; Hafshah, Mutista; Latifah, Rais Nur (Al-Kimia, 2023)
Dental caries is caused by the Streptococcus mutans bacteria, which causes a food deposit to harden and adhere to the tooth surface. Cavities will develop if food residue is not removed. Herbal plants, specifically sappan wood, can be used as an antibiotic. The purpose of this study was to look at the secondary metabolite content of sappan wood extract, antibacterial activity, and the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of sappan wood extract against Streptococcus mutans bacteria. This research method includes the maceration of sappan wood extract with 96% ethanol solvent, phytochemical screening of sappan wood extract, inhibition zone test with paper disc method, and MIC and MBC tests. Qualitative testing revealed that the sappan wood extract contained alkaloids, flavonoids, tannins, and saponins. Flavonoids, tannins, and saponins are all constituents of plants. Secang wood extract has antibacterial activity against Streptococcus mutans, as evidenced by the formation of inhibition zones at concentrations of 20%, 40%, 60%, 80%, and 100%, namely 8.75±0.354; 11±1.41;, 12.75±0.354; 16.25±0.354; and 17.5±0.000 mm. Sappan wood ethanol extract had a MIC of 12.5% against Streptococcus mutans and an MBC of 25%.